Impact of haemolysis on vancomycin disposition in a full-term neonate treated with extracorporeal membrane oxygenation - Pokorná, Pavla; Šíma, Martin; Tibboel, Dick; Slanař, Ondřej (Perfusion, 2021)
INTRODUCTION: Extracorporeal membrane oxygenation (ECMO) is a lifesaving support technology for potentially reversible neonatal cardiac and/or respiratory failure. Pharmacological consequences of ECMO-induced haemolysis in neonates are not well understood. CASE REPORT: We report a case report of a full-term neonate treated for congenital diaphragmatic hernia and sepsis with ECMO and with vancomycin. While the population elimination half-life of 7 h was estimated, fitting of the simulated population pharmacokinetic profile to truly observed drug concentration points resulted in the personalized value of 41 h. DISCUSSION: The neonate developed ECMO-induced haemolysis with subsequent acute kidney injury resulting in prolonged drug elimination. Whole blood/serum ratio of 0.79 excluded possibility of direct increase of vancomycin serum concentration during haemolysis. CONCLUSION: Vancomycin elimination may be severely prolonged due to ECMO-induced haemolysis and acute kidney injury, while hypothesis of direct increase of vancomycin levels by releasing the drug from blood cells during haemolysis has been disproved.
Keywords: Hemolysis; vankomycin; Vancomycin; hemolýza; Extracorporeal Membrane Oxygenation; lidé; mimotělní membránová oxygenace; Hernias, Diaphragmatic, Congenital; Infant, Newborn; vrozená brániční kýla; novorozenec; respirační insuficience; Respiratory Insufficiency; Humans